2023
DOI: 10.3390/molecules28010345
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Hydrothermal Preparation of Hydroxyapatite/Zinc Oxide Nanorod Nanocomposites and Their Cytotoxicity Evaluation against MG-63 Osteoblast-like Cells

Abstract: In the present study, HAp-ZnO nanorod nanocomposites were successfully prepared using a customized hydrothermal reactor and studied for their compatibility against MG-63 osteoblast-like cells. The crystallinity, morphology, presence of chemical elements, and surface area properties were studied by XRD (X-ray diffraction), FE-SEM (field emission scanning electron microscopy), TEM (transmission electron microscopy), EDS (energy dispersive spectrum) and N2 adsorption/desorption isotherm techniques, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In vitro cytocompatibility studies were investigated to predict the biological reactions of materials when applied in vivo [51]. In vitro cell viability (SRB assay) studies were performed on human osteoblast-like cell cultures (MG-63), which have the same physiology and adhesiveness as human osteoblast cells [52]. The cell viability percent against different concentrations (100 and 300 μg/ml) of BG and BG/Zn MOF samples are illustrated in Fig.…”
Section: Cytotoxicity Testmentioning
confidence: 99%
“…In vitro cytocompatibility studies were investigated to predict the biological reactions of materials when applied in vivo [51]. In vitro cell viability (SRB assay) studies were performed on human osteoblast-like cell cultures (MG-63), which have the same physiology and adhesiveness as human osteoblast cells [52]. The cell viability percent against different concentrations (100 and 300 μg/ml) of BG and BG/Zn MOF samples are illustrated in Fig.…”
Section: Cytotoxicity Testmentioning
confidence: 99%
“…[7] Previous research has shown that this approach allows for control over morphology, size, and crystal structure. [8][9][10][11] ZnO-NMts can be classified into different dimensions based on their morphology. Zero-dimensional nanomaterials, like ZnO NPs, have spherical or quasi-spherical shapes and are widely used in biomedical research.…”
Section: Introductionmentioning
confidence: 99%
“…HA is the main mineral component of hard tissues such as bones and teeth, and it exhibits excellent bioactivity, biocompatibility, and osteoconductivity [ 2 ]. HA is non-toxic and does not produce an inflammatory reaction in the body, so it is widely used in bone-filling materials, tissue engineering scaffolds, and drug carriers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%